2005
DOI: 10.1029/2005gl023081
|View full text |Cite
|
Sign up to set email alerts
|

Submicron sea spray fluxes

Abstract: [1] Eddy covariance aerosol flux measurements were conducted at the Mace Head coastal station in the North East Atlantic. Footprint and micrometeorological analysis under clean marine air mass conditions indicated that fluxes representative of open ocean conditions could be derived during high tide conditions and an oceanic fetch. Sea-spray fluxes were derived for total particle sizes larger than 10 nm and total particle sizes larger than 100 nm (i.e. covering the Aitken and Accumulation mode). The source flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
142
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 21 publications
12
142
0
1
Order By: Relevance
“…[50] To further place our results in context, we compared our measured size-resolved aerosol production efficiencies to previously reported sea spray aerosol source functions derived from both laboratory and ambient measurements using whitecap (Lab: [Fuentes et al, 2010b;Gong, 2003;Monahan et al, 1986]; Ambient: [Clarke et al, 2006]) and eddy correlation methods (Ambient: [Geever et al, 2005;Nilsson and Rannik, 2001;Norris et al, 2012]). To provide a consistent basis for this comparison, the source fluxes (number of particles produced per ocean surface area per second) were converted to production efficiencies (number of particles produced per bubble film cap area).…”
Section: Comparison With Previous Bubble-produced Aerosol Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] To further place our results in context, we compared our measured size-resolved aerosol production efficiencies to previously reported sea spray aerosol source functions derived from both laboratory and ambient measurements using whitecap (Lab: [Fuentes et al, 2010b;Gong, 2003;Monahan et al, 1986]; Ambient: [Clarke et al, 2006]) and eddy correlation methods (Ambient: [Geever et al, 2005;Nilsson and Rannik, 2001;Norris et al, 2012]). To provide a consistent basis for this comparison, the source fluxes (number of particles produced per ocean surface area per second) were converted to production efficiencies (number of particles produced per bubble film cap area).…”
Section: Comparison With Previous Bubble-produced Aerosol Studiesmentioning
confidence: 99%
“…[2010b] formulation provides particle flux as a function of seawater organic carbon (OC) concentration; two curves are presented to show production efficiency at OC concentrations of 0 and 512 mM. Integrated production efficiencies [Geever et al, 2005; are presented as individual markers, with error bars indicating the particle size range they apply over.…”
Section: Comparison With Previous Bubble-produced Aerosol Studiesmentioning
confidence: 99%
“…For coarse mode sea salt, we use the same approach as described in Stier et al (2005) with a table look-up for wind speeds between 1 and 40 m/s. The net accumulation sea-spray flux is based on Geever et al (2005) and is used as an organic-inorganic source function for the mixture of POC and sea salt aerosols. Recent measurements at the Mace Head station at the Atlantic coast of Ireland (O'Dowd et al, 2004;Yoon et al, 2007) have shown that OC contributes a considerable fraction to seaspray during periods of increased biological activity of the ocean.…”
Section: Model Set-upmentioning
confidence: 99%
“…Particles greater than 250 nm in (dry) diameter have tended to be thought of as primarily sea salt (Clarke et al, 1997) while smaller aerosol have been thought to be mainly composed of sulphates. Recent work (Nilsson et al, 2001;Geever et al, 2005) shows sea salt aerosol present below 100 nm and fluxes of particles as small as 10 nm being significant depending on sea state. It is known that both sulphate aerosol and sea-salt Published by Copernicus GmbH on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%